2022
DOI: 10.1002/anie.202201565
|View full text |Cite
|
Sign up to set email alerts
|

BTDAzo: A Photoswitchable TRPC5 Channel Activator**

Abstract: Photoswitchable reagents can be powerful tools for high-precision biological control. TRPC5 is a Ca 2 + -permeable cation channel with distinct tissuespecific roles, from synaptic function to hormone regulation. Reagents giving spatiotemporally-resolved control over TRPC5 activity may be key to understanding and harnessing its biology. Here we develop the first photoswitchable TRPC5-modulator, BTDAzo, to address this goal. BTDAzo can photocontrol TRPC5 currents in cell culture, as well as controlling endogenou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Additionally, rational approaches to increase PA signal from small molecule dyes are needed as current probe design generally relies on repurposed fluorescent dyes. [114,115] A combination of advances in these two areas will ultimately move us towards analyte-responsive PA probes that could be used to inform precision medicine efforts to individually tailor treatments to the unique biochemistry of a patient. We envision that xanthene dyes will play a pivotal role in this pursuit.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, rational approaches to increase PA signal from small molecule dyes are needed as current probe design generally relies on repurposed fluorescent dyes. [114,115] A combination of advances in these two areas will ultimately move us towards analyte-responsive PA probes that could be used to inform precision medicine efforts to individually tailor treatments to the unique biochemistry of a patient. We envision that xanthene dyes will play a pivotal role in this pursuit.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, this supports that low-ΦISC chromophores can drive highly photon-efficient assisted switching, without requiring direct triplet generation on the chromophore to initiate it (Supporting Note 9). (5) We also attempted to use the dyads' higher %E fraction at UV PSSs, compared to their isolated azobenzenes, to roughly estimate φexciplex. Although this involves weak assumptions, it indicated that φexciplex values can be similar to azobenzene ΦE→Z and ΦZ→E values (e.g.…”
Section: Mechanistic Analysismentioning
confidence: 99%
“…Azobenzenes are the major synthetic molecular photoswitches. 1 They allow chemical effectors to be actuated with high spatial and/or temporal precision, in a range of applications from photopatterned materials 2,3 to photocontrolled biology in cell culture [4][5][6][7] , in model animals 8,9 , and recently in a human clinical trial 10 . In each use, an azobenzene scaffold is decorated with substituents so that its E and Z isomers affect the system differently; and samples are locally photoswitched between majority-E and majority-Z populations to locally pattern compound activity (Figure 1a).…”
Section: Introductionmentioning
confidence: 99%
“…However, partitioning of photoswitches out of the cytosol (e.g. into lipid environments) is known to substantially impact their cellular performance; 16,39,40 such partitioning might shield StyBtz from GSH, enabling StyBtz2 to exert Z-specific bioactivity.…”
Section: Mechanism Of Action Studiesmentioning
confidence: 99%